Kinetics of Ca(OH)2 decomposition in pure Ca(OH)2 and Ca(OH)2-CaTiO3 composite pellets for application in thermochemical energy storage system. (31st December 2021) - Gupta, Aman; Armatis, Paul D.; Sabharwall, Piyush; Fronk, Brian M.; Utgikar, Vivek
Highlights: Kinetic parameters of Ca(OH)2 decomposition were estimated under different isothermal conditions. Developed rate control equations for isothermal and non-isothermal conditions for Ca(OH)2 decomposition. Enhancement of reaction rate by addition of CaTiO3 to Ca(OH)2 in the form of composite pellet. Composite pellet showed significant increase in values of activation energy and Arrhenius constant. Abstract: Thermochemical energy storage based on dehydration-hydration of Ca(OH)2 /CaO reversible gas solid reaction offers an important way of understanding energy storage/release rates of energy storage system. The aim of study is to achieve better understanding of kinetics of Ca(OH)2 decomposition under isothermal conditions and to enhance reaction rate by addition of inert agent. Thermogravimetric analyzer was used to perform kinetic analysis of pure Ca(OH)2 decomposition at various temperatures, yielding kinetic parameters - activation energy and Arrhenius constant with derived rate control equations for isothermal and non-isothermal conditions. CaTiO3 is added to Ca(OH)2 at different compositions to enhance kinetic parameters in form of composite pellets which showed significant increase in activation energy and Arrhenius constant values. Addition of CaTiO3 assisted in increasing reaction rate likely by increasing reaction surface area. Composite pellets showed promising results to get new advanced hydroxide-based material however further study on cyclic stability of the material is needed.